Inhibition of cyclin E1 overcomes temozolomide resistance in glioblastoma by Mcl‐1 degradation. Issue 8 (2nd May 2019) - Liang, Huaxin; Chen, Zhuo; Sun, Libo
Abstract: Glioblastoma (GBM) is one of the major causes of brain cancer‐related mortality worldwide. Temozolomide (TMZ) is an important agent against GBM. Acquired TMZ‐resistance severely limits the chemotherapeutic effect and leads to poor GBM patient survival. To study the underlying mechanism of drug resistance, two TMZ resistant GBM cell lines, A172 and U87, were generated. In this study, the TMZ resistant cells have less apoptosis and cell‐cycle change in response to the TMZ treatment. Western blot results revealed that cyclin E1 was upregulation in TMZ resistant cells. Inhibition or depletion of cyclin E1 re‐sensitized the resistant cells to the TMZ treatment, which indicated the induction of cyclin E1 is the cause of TMZ resistance in GBM cells. Furthermore, we also found the expression of cyclin E1 stabilized the expression of Mcl‐1, which contributes to the TMZ resistance in GBM cells. Finally, our in vivo xenograft data showed that the combination of flavopiridol, a cyclin E1/CDK2 inhibitor, overcomes the TMZ resistant by inducing higher apoptosis. Overall, our data provided a rationale to overcome the TMZ resistant in GBM treatment by inhibiting the cyclin E1 activity.